Genome wide structural prediction of ABC transporter systems in Bacillus subtilis - Mahendran, Ashwin; Orlando, Benjamin J. (Frontiers in Microbiology, 2024)
ABC transporters are a diverse superfamily of membrane protein complexes that utilize the binding/hydrolysis of ATP to power substrate movement across biological membranes or perform mechanical work. In bacteria, these transporters play essential roles in biochemical processes ranging from nutrient uptake and protein secretion to antibiotic resistance and cell-wall remodeling. Analysis of the complete genome sequence of the Gram-positive organism Bacillus subtilis has previously revealed that ABC transporters comprise the largest family of proteins across the entire genome. Despite the widespread presence of these transporters in B. subtilis, relatively few experimental structures of ABC transporters from this organism have been determined. Here we leverage the power of AlphaFold-Multimer to predict the 3-dimensional structure of all potential ABC transporter complexes that have been identified from bioinformatic analysis of the B. subtilis genome. We further classify the ABC transporters into discrete classes based on their predicted architecture and the presence or absence of distinct protein domains. The 3-dimensional structure predictions presented here serve as a template to understand the structural and functional diversity of ABC transporter systems in B. subtilis and illuminate areas in which further experimental structural validation is warranted.